(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The article provides an updated review of the data on severe acne and the treatment of this dermatosis using systemic isotretinoin. The mechanisms of action, starting and course doses, as well as issues of bioavailability of isotretinoin are discussed. The analysis of infor- mation about isotretinoin, manufactured by Lidose technology, is presented.